Application of Histomorphological Method to Assess Meat Products - Javad Sadeghinezhad; Farkhondeh Izadi; Rocco Latorre (Negah Institute for Scientific Communication, 2016)
Meat is rich in protein, minerals, and vitamins and therefore a main source of the human diet. Meat products are usually made from processed red meat and preservatives such as nitrate, to improve the overall quality of the food. Histologically, meat is mainly composed of skeletal muscle fibers, water, adipose and connective tissues. Growing bodies of evidence suggests that unauthorized ingredients or tissues in meat products are quite common, and this alters the product quality and safety.  Histological methods make it possible to examine the composition of meat products directly; hence these methodologies are largely used to detect unpermitted herbal and animal contents. Histological and histometric methods are also used to test the percentage and quality of meat in meat products. Freezing and thawing meat cause formation of ice-crystals and muscle fiber modification. This can be identified using histological methodology. Moreover, the changes in pH and mineral content in meat products can be determined using the aforementioned approach. Overall, the histomorphological approach represents a reliable method to investigate the meat product contents and make customers and markets more certain about meat quality. This brief review is focused on the use of the histological method in the assessment of meat products.